Research on the Digital Transformation Path in Engineering Education Based on AI and VR - Cai, Bao (Scientific Journal of Technology, 2025)
Under the backdrop of the Ministry of Education’s "Education Digitalization Strategy Action," this study uses the Shanghai municipal key course Tolerance, Fit and Technical Measurement as a practical vehicle to construct a new four-dimensional integrated teaching paradigm: "AI Empowerment + Knowledge Graph + Virtual Simulation + Curriculum-based Ideological Education." By integrating the Tencent IMA smart teaching platform, the DeepSeek large model, and VR experimental technology, a smart teaching closed-loop covering the entire "pre-class-in-class-post-class" process was formed. Empirical data shows that this model increased course participation to 98%, improved experiment operation accuracy by 32%, and elevated students’ overall scores by an average of 18.7%. This research provides replicable technological pathways and practical case studies for the digital transformation of engineering education.